Clinical-Nutritional Characterization Of Patients With Lung Cancer. Saturnino Lora Hospital - Bangash, Sudhair Abbas; Loei, MD, Rishubh; Abdoon Osman, Yasser Hijazi; Iqbal, Hrishik; Kanval, Sadia; Mercado, Gilberto Mercado; MPH, Rasha Alaseili (Journal of Neonatal Surgery, 2025)
Introduction: The need to implement new variables such as nutritional status in the comprehensive evaluation of patients with lung cancer for better treatment results is essential. In our context, there is insufficient evidence of the value of indicators of the nutritional status of these patients. Aim: Characterize clinical markers and nutritional status in patients with lung cancer. Material and method: An observational, descriptive, and cross-sectional study was carried out in a sample of 61 patients with lung cancer who attended the Clinical Trial consultation at the Saturnio Lora Provincial Hospital in Santiago de Cuba, between December 2015 and March 2016, where the condition was evaluated. Nutrition based on arm body composition and body mass index. Results: Women represented 47.5% and men 52.5% in total. There is a higher incidence in women between 61 and 70 years old and in men 51 and 60 years old and between 71 and 80. Concerning the muscle area, fat area, and triceps fold in the last stages of the disease there is marked evidence of depletion. This contradicts the Body Mass Index (BMI), which appears normal in the different stages. Conclusions: There was a slight predominance of men over women. The triceps fold, muscle area and fat area showed more correspondence in the nutritional evaluation of the most advanced stages of lung neoplasia concerning body mass index